A randomized controlled study of 5 and 10 days treatment with phenoxymethylpenicillin for pharyngotonsillitis caused by streptococcus group A – a protocol study. Issue 1 (December 2016) - Skoog, Gunilla; Edlund, Charlotta; Giske, Christian; Mölstad, Sigvard; Norman, Christer; Sundvall, Pär-Daniel; Hedin, Katarina
Abstract Background In 2014 the Swedish government assigned to The Public Health Agency of Sweden to conduct studies to evaluate optimal use of existing antibiotic agents. The aim is to optimize drug use and dosing regimens to improve the clinical efficacy. The present study was selected following a structured prioritizing process by independent experts. Methods This phase IV study is a randomized, open-label, multicenter study with non-inferiority design regarding the therapeutic use of penicillin V with two parallel groups. The overall aim is to study if the total exposure with penicillin V can be reduced from 1000 mg three times daily for 10 days to 800 mg four times daily for 5 days when treatingStreptococcus pyogenes (Lancefield group A) pharyngotonsillitis. Patients will be recruited from 17 primary health care centers in Sweden. Adult men and women, youth and children ≥6 years of age who consult for sore throat and is judged to have a pharyngotonsillitis, with 3–4 Centor criteria and a positive rapid test for group A streptococci, will be included in the study. The primary outcome is clinical cure 5–7 days after discontinuation of antibiotic treatment. Follow-up controls will be done by telephone after 1 and 3 months. Throat symptoms, potential relapses and complications will be monitored, as well as adverse events. Patients (n = 432) will be included during 2 years. Discussion In the era of increasing antimicrobial resistance and the shortage of new antimicrobial agents it is necessary to revisit optimal usage of old antibiotics. Old antimicrobial drugs are often associated with inadequate knowledge on pharmacokinetics and pharmacodynamics and lack of optimized dosing regimens based on randomized controlled clinical trials. If a shorter and more potent treatment regimen is shown to be equivalent with the normal 10 day regimen this can imply great advantages for both patients (adherence, adverse events, resistance) and the community (resistance, drug costs). Trial registration EudraCT number2015-001752-30 . Protocol FoHM/Tonsillit2015 date 22 June 2015, version 2. Approved by MPA of Sweden 3 July 2015, Approved by Regional Ethical Review Board in Lund, 25 June 2015.